Disparities in selective referral for cancer surgeries: implications for the current healthcare delivery system. Issue 3 (23rd March 2014) - Sun, Maxine; Karakiewicz, Pierre I; Sammon, Jesse D; Sukumar, Shyam; Gervais, Mai-Kim; Nguyen, Paul L; Choueiri, Toni K; Menon, Mani; Trinh, Quoc-Dien
Abstract : Objectives: Among considerable efforts to improve quality of surgical care, expedited measures such as a selective referral to high-volume institutions have been advocated. Our objective was to examine whether racial, insurance and/or socioeconomic disparities exist in the use of high-volume hospitals for complex surgical oncological procedures within the USA. Design, setting and participants: Patients undergoing colectomy, cystectomy, oesophagectomy, gastrectomy, hysterectomy, lung resection, pancreatectomy or prostatectomy were identified retrospectively, using the Nationwide Inpatient Sample, between years 1999 and 2009. This resulted in a weighted estimate of 2 508 916 patients. Primary outcome measures: Distribution of patients according to race, insurance and income characteristics was examined according to low-volume and high-volume hospitals (highest 20% of patients according to the procedure-specific mean annual volume). Generalised linear regression models for prediction of access to high-volume hospitals were performed. Results: Insurance providers and county income levels varied differently according to patients' race. Most Caucasians resided in wealthier counties, regardless of insurance types (private/Medicare), while most African Americans resided in less wealthy counties (≤$24 999), despite being privately insured. In general, Caucasians, privately insured, and those residing in wealthier counties (≥$45 000) were more likely to receive surgery at high-volume hospitals, even after adjustment for all other patient-specific characteristics. Depending on the procedure, some disparities were more prominent, but the overall trend suggests a collinear effect for race, insurance type and county income levels. Conclusions: Prevailing disparities exist according to several patient and sociodemographic characteristics for utilisation of high-volume hospitals. Efforts should be made to directly reduce such disparities and ensure equal healthcare delivery.